Walter Carney working in coiled wire storage at Hercules Port Ewen plant - Hercules Incorporated (1960)
General view of employee Walter Carney working in the storage area for coiled wires with attached ignition plugs, a component of the electric blasting caps manufactured at the Hercules Powder Company plant in Port Ewen, New York. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) specialized in the manufacture of explosives and smokeless powders. The company's Port Ewen plant produced a range of special detonators designed for military use, as well as construction jobs that required blasts of dynamite, such as the clearing of quarries, mines, and tunnels.
Keywords: Detonators; Employees; Chemical industry; Propellants; Hercules Incorporated; Corporations; Explosives; Carney, Walter